Dietary fiber deficiency as a component of malnutrition associated with psychological alterations in alcohol use disorder. Issue 5 (May 2021) - Amadieu, Camille; Leclercq, Sophie; Coste, Valentin; Thijssen, Victoria; Neyrinck, Audrey M.; Bindels, Laure B.; Cani, Patrice D.; Piessevaux, Hubert; Stärkel, Peter; de Timary, Philippe; Delzenne, Nathalie M.
Summary: Background & aims: Chronic alcohol consumption can cause malnutrition that may contribute to alcohol-induced organ injury and psychological disorders. We evaluated the link between nutrient intake, especially dietary fibers (DF) and different parameters reflecting mental health and well being, namely anxiety, depression, alcohol craving, sociability, fatigue and intestinal comfort in alcohol use disorder (AUD) patients. Methods: Cross-sectional data from 50 AUD patients, hospitalized for a 3-week detoxification program were used. Three 24-h recalls allowed to calculate dietary habits and nutrient intakes, that was also assessed in healthy subjects (HS). Diet quality was measured using the NOVA score. Psychological factors and intestinal discomfort were evaluated using validated self-administered questionnaires. Results: Energy intake (excluding alcoholic beverage), total fat, monounsaturated and polyunsaturated fatty acids, protein and DF intakes were lower in AUD subjects compared to HS. Ninety percent of patients had a DF intake below the recommendation. AUD patients consumed more than twice as much ultra-processed food than HS. Fructan intake was negatively associated with anxiety (p = 0.04) adjusted for main confounders. Total DF, insoluble, soluble DF and galacto-oligosaccharide intakes were associated with higher sociability score. Soluble DF intake was associated with better satisfaction of bowel function (p = 0.02) and a lower intestinal discomfort (p = 0.04). Conclusions: This study reveals that insufficient DF intake is part of AUD-related malnutrition syndrome, and is associated with higher anxiety, lower sociability score and intestinal discomfort. Our results suggest that an adequate intake of DF might be beneficial for recovery from AUD. Trial registration: NCT03803709, https://clinicaltrials.gov/ct2/show/NCT03803709 .